The Latin American (Counter-) Road Movie and Ambivalent Modernity - Kriger, Clara (Imagofagia, 2021)
Sobre Nadia Lie. The Latin American (Counter-) Road Movie and Ambivalent Modernity. New York: Palgrave Macmillan, 2017, 245 pp., ISBN: 978-3-319-43553-4.